The identity-shaping/forming role of the border/peripheral region – “kraj” – in the formation of Cossacks in Ukraine - Varga, Beáta (Études sur la Région Méditerranéenne, 2023)
In the 14th and 16th centuries, in historical sources, East Slavic people living in the southwestern territories of the Kievan Rus were called ‘Ruthenians’ or ‘Rus’ people, while their lands were referred to as ‘Ukrainian territory’. During this time period, the term ‘Ukraine’ (originating from the word ‘kraj’) referred to the borderlands lying at the southern border of the Polish–Lithuanian Commonwealth. The population of Ukraine is called a “society set for self-defence”1 in historiography, moreover, Cossacks are evaluated as a phenomenon connected and conditioned to, and intertwined with the economic and social development of the Ukrainian border area.